Risk factors of dementia: a comparative study among the geriatric age group in Ernakulam, Southern India - Lalu, Jishnu S.; Vijayakumar, Priya; George, Sobha; Nair, Amal V.; B., Arjun (International Journal Of Community Medicine And Public Health, 2018)
Background: Dementia is the global deterioration of the individual’s intellectual, emotional and cognitive faculties in a state of normal consciousness. Dementia impacts personal, family and societal life. It reduces life span, induces caregiver’s strain at family level and over utilizes health care facility. This study was aimed at describing the risk factors attributing to dementing disorders for developing preventive measures to slow down the incidence of dementia. Methods: The study was conducted in geriatrics OPD of a tertiary hospital in South India. A total of 50 dementia patients and 50 controls aged more than 65 years were selected for the study in a period of 6 months. A semi-structured questionnaire was used to collect data. Results: 40% in the age group of 65-74 years, 61% in the age group of 75-84 years and 63.6% in the age >85 years had dementia. 43.5% of males and 55.5% of females had dementia. Multivariate analysis was done to find out the independent predictors of dementia. Among the morbidities dyslipidemia 3.93 (1.12-13.87) and COPD/bronchial asthma 4.57 (1.02-20.55), less than 5 days of fruit consumption 14.98 (38-59), hearing loss 4.67 (1.15-18.91) were found to be independent risk factors for dementia. Living alone was found to be a protective factor 0.029 (0.003-0.29). Conclusions: Our study reported various risk factors of dementia that were in agreement with findings from other studies conducted in India. Avoidable risk factors such as living alone, fruit intake and control of comorbidities such as hypertension, dyslipidemia and COPD/bronchial asthma needs more attention in old age group.